"Pobre pibe", "Lindo pibe". Notas sobre Peronismo y estilística a partir de "Torito" de Julio Cortázar (1954) - Forastelli, Fabricio (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2012)
Taking as a point of departure Julio Cortázar´s “Torito”, published originally in 1954 in the magazine Buenos Aires Literaria, I aim to produce an intervention on the dilemmas opened by the tensions within literature and criticism configuring Peronism from the early 1950´s, and to reflect on some of the debates on the foundations of the lines of university criticism as well as on the critical protocols and operations on Peronism and its cultural materials.